Benchmarking Public-Private Partnerships Procurement 2017 - World Bank Group (World Bank, Washington, DC, 2016)
Many economies are yet to adopt broadly recognized good practices to prepare, procure, and manage Public-Private Partnerships (PPP). The report flags potential improvements that can help governments fill the gap in an effort to provide better PPP procurement and enable better infrastructure service delivery to all. The report benchmarks government capabilities in 82 economies across four key areas: PPP preparation, PPP procurement, unsolicited proposals, and PPP contract management.